The letter of love and concord : a revised diplomatic edition with historical and textual comments and English translation - Pogossian, Zaroui (Medieval Mediterranean, 2010)
The Letter of Love and Concord is a unique source, which allows us a glimpse into the political and religious aspirations of the Armenian Cilician elite at the end of the twelfth century, alluding to its hopes and expectations from the Crusades and the Church of Rome, as well as its uneasy relationship with the Byzantine Empire. The Letter is especially valuable for the wealth of information it contains on the royal ideology nurtured within the highest circles of the ruling Rubenid dynasty. The study provides an analysis of the sources used by its anonymous author, placing them within a histor.